2015
DOI: 10.1007/s11764-015-0478-3
|View full text |Cite
|
Sign up to set email alerts
|

Returning to work after sick leave due to cancer: a 365-day cohort study of Japanese cancer survivors

Abstract: Purpose More employees are experiencing a cancer diagnosis during their working-age years, yet there have been no largescale Japanese studies investigating sick leave due to cancer. We clarified differences in the cumulative partial and full return to work (RTW) rates between different cancer types among Japanese cancer survivors. Methods Data on Japanese employees who experienced an episode of sick leave due to clinically certified cancer diagnosed between 1 January 2000 and 31 December 2011 were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 43 publications
3
92
0
1
Order By: Relevance
“…35 Endo et al reported that 71.6% of patients experienced RTW after 6 months of sick leave, and 80.9% experienced RTW after 12 months. 36 Compared with other types of cancers, in oral cancer, the variables that are important for RTW have not been sufficiently recognized in previous studies. A lower educational level is suggested to be a risk factor for decreased RTW in workers with prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…35 Endo et al reported that 71.6% of patients experienced RTW after 6 months of sick leave, and 80.9% experienced RTW after 12 months. 36 Compared with other types of cancers, in oral cancer, the variables that are important for RTW have not been sufficiently recognized in previous studies. A lower educational level is suggested to be a risk factor for decreased RTW in workers with prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…A high proportion of employed patients with breast cancer had a RTW 36 months after treatment . Endo et al reported that 71.6% of patients experienced RTW after 6 months of sick leave, and 80.9% experienced RTW after 12 months . Compared with other types of cancers, in oral cancer, the variables that are important for RTW have not been sufficiently recognized in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…All laboratories that conducted biochemical measurements for the participating companies, however, have participated in one or more external quality control programs and received the highest rank of certification. Second, although cancer31 ) and mental health32 ) in a working population are growing concerns in Japan, we did not systematically collect data on either of these factors. Future studies should elucidate the current situations of these issues among Japanese workers.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects of this study were employees of large-scale companies who had suffered strokes. We collected anonymized data from a private occupational health center, as described in our previous study (Endo et al 2015, 2016). The occupational health center contracted occupational physicians (OP) to provide employees who belonged to a large Japanese corporate group, which included various companies (e.g., telecommunications, logistics, energy, and construction companies).…”
Section: Methodsmentioning
confidence: 99%